Image authentication using Scale Invariant Feature Transform (SIFT) / Nurul Anis Suriana Adnan - Adnan, Nurul Anis Suriana (2017)
Images plays an essential part in delivering information to the people. However, we need to have a sense of hesitation with some images due to the rise of editing tools. It is difficult to identify the authenticity of the image since they left no trace for such changes in the image. Forgery detection techniques are divided into two approaches; active and passive. The active approaches rely on pre-embedding of watermarking and signature into images while passive approaches determined by the characteristics of the image. This proposes a passive forgery detection to detect the most common type of forgery, which is copy-move attack. It copied parts of the original images and pasted it elsewhere in the same image. The proposed system is based on Scale Invariant Feature Transform (SIFT) algorithm that is invariant to translations, rotations, and scaling information in the image domain.